A luz natural lateral na concepção arquitetônica nos projetos dos edifícios residenciais do bairro paulistano de Higienópolis nos anos de 1940 1960 - Pala, Adhemar Carlos (2014)
The production of residential buildings in 1940-1960 , in São Paulo s neighborhood Higienópolis, is the main target of this research that intends to discuss the lateral natural light as one of the architectural conception elements of the buildings designed at that time , whose factors are related to cultural, economic, social and technological issues, as part of São Paulo s metropolis process. These elements had contributed to awaken the author to question about the lateral natural light on the architectural conception elements of the buildings, which were selected among dozens of significant architectural works present in Higienópolis neighborhood. The selection resulted in the following case studies: Diana Building (1954) by architect Victor Reif ; Lausanne Building (1953) by architect Adolf Franz Heep , Louveira Building (1946) of architects Giovanni Battista Vilanova Artigas and Carlos Cascaldi and Prudence Building (1944) authored by architects Rino Levi and Roberto Cerqueira Cesar . The research objectives are to identify measure and simulate the amount of natural light in the different environments of selected buildings apartments; using as a parameter the Arthur Savoy Building Code, which had served as the basis for the buildings approval with the São Paulo s City Hall. The simulations of the natural light were performed by using the computer program Relux 2011, being used which it is recommended by the NBR -15575-1 (2013) and ISO 8995-1 (2013 ) on the spot measurements with the portable equipment luximeter. The results showed that the research conducted by the Building Code are, in measurements of the spots with luximeter, in the simulations with the computer program Relux and the current NBR, which deal about the appropriate luminance for indoor, show that the modernist architects were concerned with natural lighting in architectural conception elements of the buildings.